Does the site of aspiration affect the efficacy of ultrasound-guided fine needle aspiration biopsy of thyroid nodules? - Çakmakcı, Emin; Tokgöz Özal, Safiye; Kolçak Türkoğlu, Özlem; Uçan, Berna; Kaygusuz, Umut; Dinç, Tolga; Ece, Dilek (ENT Updates, 2015)
Objective: To investigate whether the choice of a hypovascular or a hypervascular site of a thyroid nodule affects the efficacy of the ultrasound-guided fine needle aspiration procedure or not. Methods: Sixty solid thyroid nodules in 60 patients with hypo- and hypervascular parts were included in this prospective clinical study. Under color Doppler sonographic guidance, the fine needle aspiration was made with 22-gauge needle. Radiological and cytological features as well as the adequacy of samples were noted and compared. Results: Sonographically, 25 nodules (41.7%) were hetereogenous and calcified, 21 were hypoechoic (35%), 10 were isoechoic (16.7%) and 4 were hyperechoic (6.6%). Rate of adequate sampling when only hypervascular was used or hypovascular sites were evaluated were 81.7% and 83.3%, respectively. When both sites were evaluated together, rate of adequate sampling was found to be 91.7% in total. Presence and distribution of endothelial cells in the sample seems not to influence the diagnostic value of the procedure. Conclusion: Our results indicate that vascularity of a thyroid nodule outlined by color Doppler sonography can aid in optimizing the efficiency of fine-needle aspiration biopsy. The samples obtained from aspirates of hypo- and hypervascular sites are both complementary and assessment of these sites together yields better results in terms of diagnostic accuracy.